2018
DOI: 10.1080/02640414.2018.1462545
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cues in action anticipation in table tennis players

Abstract: By manipulating the congruency between body kinematics and subsequent ball trajectory, this study investigated the anticipation capabilities of regional-level, college-level, and novice table tennis players using a full video simulation occluder paradigm. Participants watched footage containing congruent, incongruent, or no ball trajectory information, to predict the landing point of the ball. They were required to choose between two potential locations to make their prediction. Percent accuracy and relevant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
1
24
1
2
Order By: Relevance
“…In the case of skilled cognitive‐motor performance, predictive theories of action observation suggest that one predicts an opponent’s actions through the processing of kinematic cues and the generation of a context‐based representation of the movement. According to this view, experienced individuals excel in the anticipation of actions that are present in their own motor repertoire (Calvo‐Merino, Glaser, Grèzes, Passingham, & Haggard, ; Cross, Hamilton, & Grafton, ; Wang et al, ; Zhao, Lu, Jaquess, & Zhou, ), and an established body of research provides robust empirical support that experienced individuals are, in fact, superior to novices in the processing of an opponent’s kinematic information and the prediction of action outcomes (Savelsbergh, Williams, Kamp, & Ward, ; Williams, Ford, Eccles, & Ward, ). This capacity, in turn, may contribute to the preservation of reactive capacity to external stimuli such as ball trajectory in the face of strategic uncertainty or the faking of movements as employed by the opponent to confuse or misdirect the performer (Hung, Spalding, Santa Maria, & Hatfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of skilled cognitive‐motor performance, predictive theories of action observation suggest that one predicts an opponent’s actions through the processing of kinematic cues and the generation of a context‐based representation of the movement. According to this view, experienced individuals excel in the anticipation of actions that are present in their own motor repertoire (Calvo‐Merino, Glaser, Grèzes, Passingham, & Haggard, ; Cross, Hamilton, & Grafton, ; Wang et al, ; Zhao, Lu, Jaquess, & Zhou, ), and an established body of research provides robust empirical support that experienced individuals are, in fact, superior to novices in the processing of an opponent’s kinematic information and the prediction of action outcomes (Savelsbergh, Williams, Kamp, & Ward, ; Williams, Ford, Eccles, & Ward, ). This capacity, in turn, may contribute to the preservation of reactive capacity to external stimuli such as ball trajectory in the face of strategic uncertainty or the faking of movements as employed by the opponent to confuse or misdirect the performer (Hung, Spalding, Santa Maria, & Hatfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies concerning anticipation in tennis or table tennis revealed that elite athletes were able to utilize early valid information to facilitate their prediction of the ball direction [5,6]. Zhao and Lu [5] found that when observing a video of table tennis serves with early kinematic cues and early flight cues, the regional-level group had higher prediction accuracy than the college-level and novice groups. To the best of our knowledge, a tennis server usually determines the ball's direction before he or she serves.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have corroborated that experienced racquet-sport players have a better anticipation ability that can predict the outcomes of the movements of their opponents and even the ball trajectory. 3235 Based on this finding, it can be speculated that PA possessed a better ability of flexible motions than BP which would be beneficial for themselves to improve the quality of stroke. Additionally, compared with BP at the event of FE, PA showed larger rear-foot internal rotation and forefoot abduction.…”
Section: Discussionmentioning
confidence: 93%